Cell-wall deficient L. monocytogenes L-forms feature abrogated pathogenicity - Schnell, Barbara; Staubli, Titu; Harris, Nicola L.; Rogler, Gerhard; Kopf, Manfred; Loessner, Martin J.; Schuppler, Markus (Frontiers in Cellular and Infection Microbiology, 2014)
Stable L-forms are cell wall-deficient bacteria which are able to multiply and propagate indefinitely, despite the absence of a rigid peptidoglycan cell wall. We investigated whether L-forms of the intracellular pathogen L. monocytogenes possibly retain pathogenicity, and if they could trigger an innate immune response. While phagocytosis of L. monocytogenes L-forms by non-activated macrophages sometimes resulted in an unexpected persistence of the bacteria in the phagocytes, they were effectively eliminated by IFN-γ preactivated or bone marrow-derived macrophages. These findings were in line with the observed down-regulation of virulence factors in the cell-wall deficient L. monocytogenes. Absence of IFN-β triggering indicated inability of L-forms to escape from the phagosome into the cytosol. Moreover, abrogated cytokine response in MyD88-deficient dendritic cells challenged with L. monocytogenes L-forms suggested an exclusive TLR-dependent host response. Taken together, our data demonstrate a strong attenuation of Listeria monocytogenes L-form pathogenicity, due to diminished expression of virulence factors and innate immunity recognition, eventually resulting in elimination of L-form bacteria from phagocytes.